COVID-19 study in rural areas of Guatemala: Long-term impacts on food security and nutrition in the Western Highlands - Hernandez, Manuel A.; Ceballos, Francisco; Paz, Cynthia; Berrospi, Maria Lucia (International Food Policy Research Institute, 2022)
Since the beginning of the COVID-19 pandemic, Guatemalan farmers have endured multiple challenges brough about by national and local restrictions to movement as well as disruptions in agricultural value chains. Similarly, farmers have been exposed to several external shocks such as ETA and IOTA tropical storms that hit the country in late 2020 and the recent conflict in East Europe and price crisis. This study examines the long-term effects of the COVID-19 environment on the food security and nutrition of rural households in the Western Highlands of Guatemala. The analysis is based on information from a panel of 1,262 smallholder households in the departments of Huehuetenango, Quiche, and San Marcos, collected during four survey rounds during November-December 2019 (face-to-face), May-June 2020 (by phone), May-June 2021 (by phone), and May-June 2022 (by phone). The study places special emphasis on evaluating changes in agricultural and non-agricultural income sources —including remittances—, and changes in dietary diversity —including consumption of animal-sourced foods (ASF) and fruits and vegetables (F&V)— at the household level, as well as among women between 15 and 49 years and children between 6 and 23 months. The results show some improvements in 2022 in income, food security and household dietary patterns in relation to previous years, but the levels are still lower than those reported before the pandemic (in 2019). The study also explores the effect of recent changes in the availability and prices of agricultural inputs faced by the smallholders as a result of the war between Ukraine and Russia, among other factors.